2013
DOI: 10.1080/15374416.2012.738454
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Exposure Sessions as Predictors of Treatment Response in Anxious Youth

Abstract: Guidelines for conducting effective exposure treatment with anxious youth emphasize preparation for and processing of the exposure task as important elements, but limited research has examined these guidelines. Using multiple regression, this study evaluated the extent to which independent observers' ratings of preparation and processing of in-session exposure tasks were associated with treatment outcome in a sample of 61 anxiety-disordered youth. Results indicated that preparation for exposure was not related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 46 publications
3
41
3
Order By: Relevance
“…They should also help the client understand that, as in life, there are no guarantees of safety or otherwise in exposures. Olatunji et al (2009, p. 176) explain that risks can be minimized by anticipating the possibility that exposures may not go as planned and framing exposures as a test of “probabilities, predictions and costs.” Furthermore, therapists may wish to consider extended sessions for clients who need extra time to process an exposure (Tiwari, Kendall, Hoff, Harrison, & Fizur, 2013). Nevertheless, they should discuss habituation as an outcome that is possible but not definite, and should instead emphasize the goals of being able to tolerate the anxiety and testing specific anxious predictions while improving functioning (Craske et al, 2008).…”
Section: Beneficence and Nonmaleficencementioning
confidence: 99%
“…They should also help the client understand that, as in life, there are no guarantees of safety or otherwise in exposures. Olatunji et al (2009, p. 176) explain that risks can be minimized by anticipating the possibility that exposures may not go as planned and framing exposures as a test of “probabilities, predictions and costs.” Furthermore, therapists may wish to consider extended sessions for clients who need extra time to process an exposure (Tiwari, Kendall, Hoff, Harrison, & Fizur, 2013). Nevertheless, they should discuss habituation as an outcome that is possible but not definite, and should instead emphasize the goals of being able to tolerate the anxiety and testing specific anxious predictions while improving functioning (Craske et al, 2008).…”
Section: Beneficence and Nonmaleficencementioning
confidence: 99%
“…This AMS followed by exposure model (AMS-Ex) has dominated the CADs literature since the mid-1990s to the extent that 93 % of studies in a recent meta-analysis used this approach (Reynolds et al 2012), including the largest randomized controlled trial (RCT; Walkup et al 2008). Among the treatment components, there is a general consensus that exposure is the active ingredient (Barlow 1988;Beidel et al 2000;Carey 2011;Clark 1999;Crawley et al 2012;Davis and Ollendick 2005;Kazdin and Weisz 1998;Kendall et al 2005;Marks 1969;Silverman and Kurtines 1996) supported by the link between more exposure practice and better outcomes for CADs (Tiwari et al 2013;Vande Voort et al 2010). However, the ordering of AMS prior to exposure is based on the untested assumption that children require AMS to change maladaptive cognitions (Crawley et al 2012;Kendall 1985;Kendall et al 1997) or to tolerate exposure (Manassis et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In an RCT comparing Family-Focused CBT (FCBT) and ChildFocused CBT, Wood, McLeod, Piacentini, and Sigman (2009) reported that there was a significantly greater reduction in parental intrusiveness in the FCBT group than in the Child-Focused CBT group from pre-to posttreatment and that in a moderated mediation model, age HIGA-MCMILLAN ET AL. moderated this mediation effect such that FCBT was associated with decreased intrusiveness for early adolescents but not for children. Further, in the only study examining exposure practices in an RCT, Tiwari, Kendall, Hoff, Harrison, and Fizur (2013) reported that postexposure processing of the exposure task, receiving a reward following an in vivo exposure, and being assigned an exposure homework task predicted better outcomes, whereas more preparation prior to the in vivo exposure task did not. Tiwari and colleagues theorized that postevent processing produced better outcomes because of the shift in cognitions that happens during postexposure processing.…”
Section: Mediators and Moderators Of Treatment Outcomementioning
confidence: 99%
“…This is a very important next step in treatment outcome research, as it is very possible that incremental learning could be critical such that learning Technique A then Technique B, followed by Technique C, in this particular order, provides the most improvement. It is also possible that some techniques work better together, whereas others may serve to contradict one another (e.g., as previously noted more cognitive preparation prior to exposure does not predict better outcomes; Tiwari et al, 2013). Isolating key ingredients and sequences of these ingredients via dismantling or other advanced RCT approaches (e.g., Sequential Multiple Assignment Randomized Trial; Collins, Murphy, & Strecher, 2007) will be important over the next decade of treatment outcomes research for youth anxiety.…”
Section: Anxiety Disorders Update 105mentioning
confidence: 99%